Effect of Temperature on Fretting Wear Behavior of Inconel 718 Alloy - HE Jifan, JIN Jin, LIU Jianhua, PENG Jinfang, ZHU Minhao (Cailiao Baohu)
Inconel 718 superalloy has been widely used in the fields of aerospace， gas turbine and nuclear energy， etc.In order to evaluate its fretting wear performance under actual service conditions， tangential fretting wear tests of Inconel 718 superalloy at different temperatures were carried out by using a self-developed high temperature fretting wear rig.The micro motion behavior，material damage response and wear mechanism of materials at different environmental temperatures were studied and revealed.Results showed that the operating temperature had a great influence on the fretting wear characteristics and damage mechanism of the Inconel 718 alloy.Under different displacement amplitudes，the fretting wear shifted towards the direction of gross slip regime with the increase of ambient temperature.The wear mechanism of the fretting partial slip regime was mainly adhesive wear， the material adhesion intensified with the increase of temperature， and the fretting state changed to the mixed regime with the temperature rising to 600 ℃.In the fretting mixed regime or slip regime， the damage mechanism changed from fatigue wear at lower temperatures (room temperature and 200 ℃) to adhesive wear and abrasive wear at higher temperatures (400 ℃and 600 ℃)，and the oxidation wear intensified.Moreover， the increase in ambient temperature would exacerbate the fretting damage of materials to varying degrees， and the wear rate at high temperature was about 1.76～18.60 times of that at room temperature.In addition， the temperature threshold for the maximum wear rate caused by different displacement amplitudes also varied.The research results provide theoretical data and application reference for anti-fretting damage protection of Inconel 718 alloy at different service temperatures.